Functional recovery induced by KCC2-enabled relay pathways in completely injured spinal cords in adult rats - Yaxian Wang; Fenglan Liu; Qi Shan; Xuzhaoyu Wang; Wei Liu; Xinxin Chen; Cheng Teng; Yehua Lv; Xiaosong Gu; Xuhua Wang; Bin Yu (Proceedings of the National Academy of Sciences, 2025)
Despite tremendous progress in promoting endogenous axon regeneration and engineering relay pathways by cell transplantation, the obtained functional recovery is still limited. We reason that these regenerated connections might not be able to integrate into the functional circuits in injured spinal cord. In this study, we tested whether modulating the neuronal excitability by pharmacological potassium–chloride cotransporter (KCC2) activation could enhance the functional outcomes of these regenerative treatments in a complete spinal cord injury (SCI) in adult rats. We found that while osteopontin/insulin-like growth factor 1 overexpression (to enhance axon regeneration) or neural stem cell (NSC) transplantation (to build a relay) alone failed to restore the interrupted spinal circuitry, the double treatment facilitated the integration of NSCs into the host spinal network, significantly promoting axonal regeneration and synapse formation. Behavioral assessments demonstrated that the addition of CLP290, a KCC2 agonist, to the combined treatment markedly improved hindlimb locomotion, as evidenced by higher Basso, Beattie and Bresnahan (BBB) scores and enhanced joint oscillation in fine locomotion analysis. Consistently, electrophysiological evaluations indicated partial restoration of electrical transmission through the reconstructed spinal network. Our findings highlight the synergistic effects of KCC2-mediated neuronal modulation on promoting functional recovery after complete SCI.